Relationship between physical factors and change of direction speed in team sports - Horníková, H.; Zemková, E. (Applied Sciences, 2021)
The relationship between the change of direction speed (CODS) and sprint speed, jump ability, and muscle strength is well recognized. However, the strength of this relationship may depend on how the test is designed and which parameters are analyzed. This scoping review aims to: (1) map the literature that addresses the relationships between the CODS and physical fitness and performance variables in players of team sports; (2) specify the limiting factors of CODS; and (3) identify gaps in existing literature and propose future research on this topic. Altogether, 22 research studies met the defined inclusion criteria. Most studies revealed significant correlations between CODS and sprint speed, muscle strength, and jump ability. This relationship was mainly demonstrated between CODS and linear sprint speed for 30 m (r = 0.60 to 0.74), 10 m (r = 0.39 to 0.65), maximal leg strength (r = -0.51 to -0.89), particularly explosive (r = -0.44 to -0.81), and reactive strength (r = -0.37 to -0.65). However, the strength of this relationship depends on the type of CODS test, its structure (total running distance, number of changes in direction), and parameters analyzed (height, power, velocity, and relative or absolute values). The recommendation for future research is to focus on choosing the test and its parameters to be close to the fitness demands of the particular sport.